Quality of guidelines on the management of diabetes in pregnancy: a systematic review - Greuter Marjolein JE; van Emmerik Nathalie MA; Wouters Maurice GAJ; van Tulder Maurits W (BMC, 2012)
Abstract Background Diabetes during pregnancy can lead to severe risks for both mother and fetus when it is not managed properly. The use of rigorously developed guidelines with a robust implementation process can have a positive influence on the management of diabetes during pregnancy. This study aims to compare recommendations and assess the quality of clinical guidelines on gestational diabetes mellitus (GDM) and pre-existing diabetes mellitus during pregnancy. Methods Guidelines were selected by searching PubMed, the Guideline Clearing House and Google. All guidelines developed since 2000 on diabetes during pregnancy in English or Dutch were considered. Recommendations of the guidelines were compared. Furthermore, the quality was assessed by two authors independently, using the AGREE instrument. Results Eight guidelines were included. According to the AGREE instrument, the quality of most guidelines was low. The domains editorial independence, stakeholder involvement and rigour of development had the lowest scores. Recommendations were mainly comparable on glycemic control, preconceptional counseling and prenatal care and labour. Differences between recommendations were found for screening on GDM and induction of labour. Conclusions The quality of most guidelines concerning the management of diabetes during pregnancy needs to be improved. A more systematic approach in the development of these guidelines, more attention for updating procedures and piloting of the guidelines and involvement of target users and patients is recommended.